Event-Related Potentials of Bottom-Up and Top-Down Processing of Emotional Faces - Afsane Moradi; Seyed Abolghasem Mehrinejad; Mohammad Ghadiri; Farzin Rezaei (Basic and Clinical Neuroscience, 2017)
Introduction: Emotional stimulus is processed automatically in a bottom-up way or can be processed voluntarily in a top-down way. Imaging studies have indicated that bottom-up and top-down processing are mediated through different neural systems. However, temporal differentiation of top-down versus bottom-up processing of facial emotional expressions has remained to be clarified. The present study aimed to explore the time course of these processes as indexed by the emotion-specific P100 and late positive potential (LPP) event-related potential (ERP) components in a group of healthy women. Methods: Fourteen female students of Alzahra University, Tehran, Iran aged 18–30 years, voluntarily participated in the study. The subjects completed 2 overt and covert emotional tasks during ERP acquisition. Results: The results indicated that fearful expressions significantly produced greater P100 amplitude compared to other expressions. Moreover, the P100 findings showed an interaction between emotion and processing conditions. Further analysis indicated that within the overt condition, fearful expressions elicited more P100 amplitude compared to other emotional expressions. Also, overt conditions created significantly more LPP latencies and amplitudes compared to covert conditions. Conclusion: Based on the results, early perceptual processing of fearful face expressions is enhanced in top-down way compared to bottom-up way. It also suggests that P100 may reflect an attentional bias toward fearful emotions. However, no such differentiation was observed within later processing stages of face expressions, as indexed by the ERP LPP component, in a topdown versus bottom-up way. Overall, this study provides a basis for further exploring of bottomup and top-down processes underlying emotion and may be typically helpful for investigating the temporal characteristics associated with impaired emotional processing in psychiatric disorders.